2009
DOI: 10.1002/ptr.3082
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Korean red ginseng extract on cisplatin ototoxicity in HEI‐OC1 auditory cells

Abstract: Ginseng extract is known to have many beneficial effects, including the reversal of pathological and physiological changes induced by ischemia, stress, and aging. Cisplatin, an effective antineoplastic drug, can cause irreversible sensorineural hearing loss and serious tinnitus in humans; thus cisplatin-induced ototoxicity is a useful experimental model for ototoxicity. This study investigated the protective effects of Korean red ginseng extract on cisplatin-induced ototoxicity in auditory cells. Pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 17 publications
0
43
1
Order By: Relevance
“…KRG extracts, or its specific saponins, were shown to have antiapoptotic and antioxidant properties in various tissues both in vitro and in vivo [8] . Recently, it was shown that KRG has otoprotective properties against gentamicin [9,10] , 3-nitropropionic acid [12] , and CDDP-induced ototoxicity [8,13] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…KRG extracts, or its specific saponins, were shown to have antiapoptotic and antioxidant properties in various tissues both in vitro and in vivo [8] . Recently, it was shown that KRG has otoprotective properties against gentamicin [9,10] , 3-nitropropionic acid [12] , and CDDP-induced ototoxicity [8,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that KRG has otoprotective properties against gentamicin [9,10] , 3-nitropropionic acid [12] , and CDDP-induced ototoxicity [8,13] . These studies revealed that KRG mainly works by inhibition of some proapoptotic genes such as caspase-1, caspase-3, and the TNF family of genes and by enhancement of antiapoptotic gene expression such as bcl-2 [8][9][10][11][12][13] . On the other hand, KRG has antiapoptotic effects on neuronal tissues [18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cisplatin ototoxicity emerges as symmetrical hearing loss in which particularly high frequencies are irreversibly affected. Many antioxidant agents such as sodium thiosulfate, N-acetylcysteine, acetyl-L-carnitine, Korean red ginseng, and resveratrol have been tested in vitro and in vivo in order to prevent this irreversible side effect (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%